Experimental Studies of Hydraulic Losses and Carbon Dioxide Concentration in The Space Under The Face Mask Protecting Against Covid-19 - Teleszewski, Tomasz Janusz; Gładyszewska-Fiedoruk, Katarzyna; Sulewska, Maria Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Masks are the primary tool used to prevent the spread of COVID-19 in the current pandemic. Tests were carried out to determine the total pressure drop through the materials from which the masks are made and the correlation of these results with the concentration of carbon dioxide in the inner space of the mask.
Keywords: face masks; COVID-19; hydraulic losses; mask material; carbon dioxide concentration; maski na twarz; straty hydrauliczne; materiał maski; stężenie dwutlenku węgla